Effects of phase‐transited lysozyme on adhesion, migration and odontogenic differentiation of human dental pulp cells: An in vitro study. (6th January 2023) - Zhao, Jiange; Zhou, Yunjie; Yan, Jinjie; Liu, Jie; Wang, Linxian; Zhang, Xu; Lou, Yaxin; Que, Kehua
Abstract: Aim: To explore the effects of phase‐transited lysozyme (PTL) coated dentine slices on cell adhesion, migration and odontogenic differentiation of human dental pulp cells (HDPCs). Methodology: Cell growth and cell cycle analysis were conducted to verify the biocompatibility of PTL for HDPCs. Cell adhesion, cell morphology and proliferation were explored by DiI staining, Scanning electron microscopy and MTT assay. Cell migration was investigated by Transwell assay. The effects of PTL on odontogenesis and mineralization of HDPCs were assessed by real‐time quantitative polymerase chain reaction and Western blot. The mineralization of HDPCs was evaluated by Alizarin red staining. HDPCs were isolated from extracted third molars. The level of statistically significant difference was accepted at p  < .05. Results: PTL showed no negative effect on cell cycle of HDPCs and compared with the blank group, HDPCs labelled with DiI staining showed significantly more adhered cells at 48 h ( p  < .05), extending cell processes and more finger‐like or reticular pseudopodia on PTL‐coated dentine slices. The results of MTT and Transwell assay showed that PTL promoted the proliferation ( p  < .05) and migration ( p  < .01) of HDPCs, respectively. Compared with the blank group, the gene expression of dentine sialophosphoprotein (DSPP), osteopontin and bone sialoprotein in HDPCs cultured on PTL was significantly upregulated on day 3 and 7 ( p  < .05), while the protein expression of DSPP showed no significant change on both day 7 and day 14. Alizarin red staining showed that PTL promoted more mineralization nodules formation of HDPCs ( p  < .05). Conclusions: PTL promoted the adhesion, proliferation and migration of HDPCs on dentine slices, and positively affected odontogenic differentiation and mineralization of HDPCs.